Greek Yogurt and 12 Weeks of Exercise Training on Strength, Muscle Thickness and Body Composition in Lean, Untrained, University-Aged Males - Bridge, Aaron; Brown, Joseph; Snider, Hayden; Nasato, Matthew; Ward, Wendy E.; Roy, Brian D.; Josse, Andrea R. (Frontiers in Nutrition, 2019)
Milk and/or whey protein plus resistance exercise (RT) increase strength and muscle size and optimize body composition in adult males and females. Greek yogurt (GY) contains similar muscle-supporting nutrients as milk yet it is different in several ways including being a semi-solid food, containing bacterial cultures and having a higher protein content (mostly casein) per serving. GY has yet to be investigated in this context. The purpose of this study was to assess the effects of GY consumption plus RT on strength, muscle thickness and body composition in untrained, university-aged males. Thirty males (20.6 ± 2.2 years) were randomized to 2 groups (n=15/group): fat-free, plain GY or a Placebo Pudding (PP; isoenergetic carbohydrate-based pudding), and underwent a combined RT/plyometric training program 3days/week for 12 weeks. They consumed either GY (20 g protein/dose) or PP (0 g protein/dose) daily, 3 times on training days and 2 times on non-training days. After 12 weeks, both groups significantly increased strength, muscle thickness and fat-free mass (FFM) (p<0.05). The GY group gained more total strength (GY; 98±37 kg, PP; 57±15 kg), more biceps brachii muscular thickness (GY; 0.46±0.3 cm, PP; 0.12±0.2 cm), more FFM (GY; 2.4±1.5 kg, PP; 1.3±1.3 kg) and reduced % body fat (GY; -1.1±2.2 %, PP; 0.1±2.6 %) than PP group (p<0.05 expressed as absolute change). Thus, consumption of GY during a training program resulted in improved strength, muscle thickness and body composition over a carbohydrate-based placebo. Given the benefits of consuming GY and its distinctiveness from milk, GY can be a plausible, post-exercise, nutrient-rich alternative for positive strength, muscle and body composition adaptations.